Friends for life. (RIBA Journal, 2006)
The article focuses on the views of Robert Adam on the sustainability of building designs in Great Britain. According to Adam, the longevity and the fashion affects building designs. He elaborates that durability, sustainable structural designs and the kind of building materials promotes the life of a building. He adds that buildings should be serviced easily and lit naturally for it to sustain a longer period.